Analisis Penerapan E-Korespondensi Pada PT X - Novinda Elisia; Marsofiyati Marsofiyati; Terrylina Arvinta Monoarfa (Politeknik Kampar, 2023)
This research was conducted at PT X which aims to find out the implementation, the impact of the implementation and the effectiveness of implementing e-Correspondence according to the views of employees at PT X. In this study the authors used a qualitative method with a case study approach. Data collection techniques used are interviews, observation and literature study. This data analysis technique includes data reduction, data presentation and drawing conclusions. The results obtained in this study are that the use of e-correspondence at PT X has not been implemented optimally, as evidenced by the presence of several obstacles that occur. Therefore, regular implementation must be optimized so that employees have a basis for carrying out effective correspondence activities.